21.4k views
3 votes
Please help guys
I will be helping u in the days to come n follow u for sure​

Please help guys I will be helping u in the days to come n follow u for sure​-example-1
User OznOg
by
5.8k points

2 Answers

4 votes

Answer:

Explanation:


(cot \theta)/(cosec \theta + 1) = \frac{cosec\theta -1} {cot \theta}


L H S


(cot \theta )/(cosec \theta + 1 ) * (cosec \theta - 1)/(cosec \theta -1)
[ \ multiplying \ and \ dividng \ by \ (cosec \theta - 1) \ ]


= (cot \theta * (cosec \theta - 1))/((cosec ^2\theta -1))
[ \ (a -b)(a+b) = a^2 - b^2 \ ]


= (cot \theta * (cosec \theta - 1))/(cot^2 \theta)\\ \\
[ \ cosec^2\theta - 1 = cot^2 \theta \ ]


= (cosec \theta - 1 )/(cot \theta) \\\\= RHS

User JD Frias
by
6.0k points
4 votes

Answer:

I'd 7587163850

Pass 123456

Join

User Ewe Tek Min
by
5.5k points